Síntese de 2-(1,4,5,6-tetraidropiridin-3-il)-2-oxoacetato de etila 1,6-dissubstituídas via mecanismo ANRORC - Pretto, Leida de Mendonça (2013)
This paper presents a synthetic strategy for the preparation of two series of novel 1,6-disubstituted Ethyl 2-(1,4,5,6-tetrahydropyridin-3-yl)-2-oxoacetate from the reaction of the cyclic enone ethyl 2-(6-ethoxy-5 ,6-dihydro-4H-pyran-3-yl)-2-oxoacetate and aryl amines as precursors, following an ANRORC type mechanism. The substituents of the amines are the flowing: C6H5, C6H4-4-Cl, 3-Cl-C6H4,-C6H3 3,4-Cl 2,4-Cl-C6H3 3-F-C6H4, 2-F-C6H4 3-Me-C6H4, 2-OMe-C6H4, 4-Br-C6H4. The ethyl 1-aryl-6-arylamino-2-(1,4,5,6-tetrahydropyridin-3-yl)-2-oxoacetate were synthesized in a simple procedure, using room temperature and 24 h as the reaction condition. The products from this series were obtained with satisfactory yields between 45-93% and the purification thereof was performed by recrystallization. To obtain the Ethyl 1-amino-6-ethoxy-2-(1,4,5,6-tetrahydropyridin-3-yl)-2-oxoacetate the ethyl 2-(1,4,5,6-tetrahydropyridin-3-yl)-2-oxoacetate was reacted withan equivalent of primary amine in ethanol and an equivalent of pyridine was required. The reaction was refluxed for 48h. Purification of this series of compounds was accomplished by eluting the compound through a chromatographic column. The products were obtained in good yields ranging from 66-86%.